Pemasaran Gabah dan Pengaruhnya terhadap Kondisi Sosial Ekonomi Petani di Kabupaten Nganjuk - Nyasa Aji Hariyanto; Widi Artini; Tutut Dwi Sutiknjo; Nur Laely; Difa Pramudita Sari (Universitas Kadiri, 2023)
Grain can be marketed in harvested or milled dry unhusked form. The farmer's decision to sell these two types of products impacts their socio-economic status, as happened to the rice farmers in Tiripan Village. The research was carried out at this location to understand the rice marketing mechanism, evaluate the difference in income received by farmers for the two types of products, and analyze the impact of the marketing system for the two types of products on the socio-economic conditions of farmers. The sample was selected at random with a stratification of 30 respondents. Most respondents sold unhusked rice directly in the dry harvested form, although a small proportion sold it in milled form with a wholesale or daily harvesting workforce. Data were analyzed descriptively by calculating farming analysis and the average difference test (t-test). The average income of farmers with the dry mill system is greater, with a difference of IDR1,303,983 per hectare from the dry harvest. In this context, improving the selling system of rice grain in the Nganjuk Regency is necessary. Adequate infrastructure development, such as efficient transportation facilities and good roads, needs to be done to facilitate farmers' access to milling factories. In addition, it is also necessary to develop farmer cooperatives or farmer groups that can act as fair and transparent intermediaries between farmers and milling factories. Gabah dapat dipasarkan dalam bentuk kering saat panen atau kering setelah giling. Keputusan petani untuk memasarkan kedua jenis produk ini berdampak terhadap sosial ekonomi mereka, sebagaimana yang terjadi pada petani padi di Desa Tiripan. Penelitian dilangsungkan di lokasi tersebut untuk memahami mekanisme pemasaran padi, mengevaluasi perbedaan pendapatan yang diterima petani atas kedua jenis produk, serta menganalisis dampak dari sistem pemasaran kedua jenis produk terhadap kondisi sosial ekonomi petani. Sampel dipilih secara acak berstratifikasi sebanyak 30 responden. Mayoritas responden menjual gabah langsung dalam bentuk kering panen, meski sebagian kecil menjual dalam bentuk giling dengan tenaga kerja panen yang bersifat borongan atau harian. Data dianalisis secara deskriptif dengan perhitungan analisis usahatani dan uji beda rata-rata (uji-t). Rata-rata pendapatan petani dengan sistem kering giling lebih besar dengan selisih sebesar Rp1.303.983 per hektar dari kering panen. Dalam konteks ini, perlu dilakukan upaya untuk meningkatkan sistem penjualan gabah padi di Kabupaten Nganjuk. Pembangunan infrastruktur yang memadai, seperti sarana transportasi yang efisien dan jalan yang baik, perlu dilakukan untuk memfasilitasi akses petani ke pabrik penggilingan. Selain itu, perlu juga adanya pengembangan koperasi petani atau kelompok tani yang dapat berperan sebagai perantara yang adil dan transparan antara petani dan pabrik penggilingan.